Tying decentralization and income redistribution to fight corruption: Empirical evidence from developed and developing countries - Bojanic, Antonio N. (Frontiers in Applied Mathematics and Statistics, 2023)
Utilizing a panel data set for OECD and non-OECD countries for the period 1980 to 2016, I analyze the effects on corruption of interacting different forms of decentralization – fiscal, administrative, political, and overall decentralization – with an indicator of income inequality. The findings demonstrate that fiscal, administrative, and overall decentralization by themselves are not conducive to lowering corruption, but when moderated by the Gini index, corruption levels decrease in all countries. Moreover, as income inequality decreases, the impact of these forms of decentralization in lowering corruption increases, highlighting that decentralization can be an effective tool in combating corruption particularly when income inequality improves. The findings also demonstrate that in non-OECD countries, decentralization is an important tool to fight corruption up to high levels of inequality, proving that decentralization in developing countries is essential even when issues of income distribution have not been fully solved.